Two new subspecies of the leaf-tailed gecko Phyllurus ossa (Lacertilia: Carphodactylidae) from mid-eastern Queensland, Australia - Couper, Patrick; Hoskin, Conrad J. (Zootaxa, 2013)
Following the discovery of a new population of Phyllurus ossa on Whitsunday Island in the Cumberland Island Group, eastern Queensland, we conducted both genetic and morphological analyses to assess differences between all known pop-ulations. The analyses revealed three genetically distinct, morphologically diagnosable, geographical units. The differenc-es are such that we recognise these as subspecies: Phyllurus ossa ossa restricted to the Mt Ossa/Mt Pelion/ Mt Charlton/ St Helens Gap area; P. ossa hobsoni subsp. nov. on Mt Dryander and in the Conway Range and P. ossa tamoya subsp. nov. currently only known from Whitsunday Island. There are now 11 recognised taxa in Phyllurus. The three P. ossa sub-species are narrowly distributed and closely associated with exposed rock in low to mid-elevation vine forests. Their cur-rent distributions are shaped by past climate change that progressively contracted and fragmented the distribution of rainforests in eastern Australia. The recognition of these subspecies has land management/conservation implications.